Amygdalus ledebouriana Schlecht. in conditions of culture in the dendopark "Askania-Nova" (CHORNOMORSKI BOTANICAL JOURNAL, 2019)
The success introduction of the Amygdalus ledebouriana Schlecht with international sozological status in the dendrological park "Askania-Nova" was analyzed. It has a high level of adaptation to regional natural and climatic conditions. Plant height is from 1.1 m to 1.3 m. Average size of leaves is 4.3±0.12 sm × 1.1±0.08 sm, perianthes of leaves – 0.96±0.09 cm × 0.56±0.05 sm, stone-fruits – 2.5±0.08 sm × 2.1±0.1 sm, stones – 1.9 0.07 sm × 1.4±0.06 sm. The weight of 100 units medium-sized stones is 89.9 g. Amygdalus ledebouriana belongs to plant with an early onset of vegetation renewal. The dendro-rhythm type is a early-middle and time of the flowering is a early-spring. The duration of the growing season is 213–232 days. The phenological lag is 131–133 days from the beginning of flowering to the full ripening of the fruits. Growth of shoots is 92±11 days. The annual growth of shoots is stable 15.5±0.7 – 16.1±0.7 sm. It blooms abundantly every year and bears fruit in single years. It form viable fruits which have high soil germination in some methods of preplant preparation. The species is characterized by a high vegetative reproductive ability, due to which it increases its living space and is fixed on new places of growth. A. ledebouriana is characterized by significant winter hardiness in the dendropark and drought resistance from medium to high range (usually the tips of the leaves are "burned", sometimes the leaves turn yellow). In some years, the leaves are affected by spot hole disease (Clasterosporium carpophilum), and some shoots by brown rot disease (Monilinia). Damage to other plant organs and other biotic factors were not observed.
Keywords: vegetation duration, morphometric parameters of vegetative and generative organs, natural regeneration, reproduction.